Effect of Aeration Treatment on Methylene Blue Removal Using TiO2-Zeolite - Pratama, Nanda Alzeta; Artsanti, Pedy (Proceeding International Conference on Science and Engineering, 2019)
Effect of aeration treatment on Methylene Blue (MB) removal using TiO2-Zeolite has been investigated. The TiO2-Zeolite was prepared by mixing activated zeolite and TiO2 in absolute ethanol. This composite was characterized using Fourier Transform Infrared (FT-IR) and X-Ray Diffraction (XRD). The MB removal was monitored spectrophotometrically. The effect of contact time, composite mass, and aeration treatment on MB removal was observed. Characterization results showed that there was interaction between TiO2 and SiO/AlO of zeolite. The observation of aeration treatment using oxygen exhibited significant improving on MB removal.